Perencanaan Belt Conveyor System Sebagai Alat Angkut Box dengan Kapasitas 20 Ton/Jam - Putri Sundari; Wardjito; Sa’ad Bayu Hariyono (Wahana Teknik, 2020)
The study aimed to design belt conveyor system for box transportation with capacity 20 Ton/hours with the horizontal line distance 20 m. This study located in PT. Intan Ustrix, Jl. Roomo No. 425 Manyar, Gresik, Jawa Timur. The results of calculation showed that belt conveyor needs specifications: rubber width 650 mm, speed of belt converter 1 m/s, driver motor power 0,699 kW, and installed motor power 2,2 kW. Head (drive) pulley diameter 500 mm, shaft diameter 125 mm, tail pulley diameter and take-up pulley 400 mm, bend pulley and snub up pulley diameter is 250 mm. Specification of rubber belt conveyor is fabric type and general (M) 1.200 mm, EP 630/4 Ply. Specification of electrical motor are 2,2 kW, 380 V, 3 Phase, 50 Hz, 4 Poles, Speed 1500 rpm, with gear box specification (reducer) is bofiglioli VF 72, with ratio 1:40. Keywords: Belt Conveyor, Box Transportation, Design.